مظاهر الانتباه وزمن رد الفعل وعلاقتهما ببعض المتغيرات الفسيولوجية لدى المصارعين والملاكمين - الحوالة، سمير محمد محمود Alhawala, Samir Mohammed Mahmoud (جامعة مدينة السادات - كلية التربية الرياضية, 2013)
This study aims to identify the differences and correlations among attention aspects level; reaction time (RT), and physiological variables (PV) of study for wrestlers and boxers. The researchers used descriptive survey method and applied the study on subjects of some Menofia clubs (18-24) aged. Sample of study included (20) of subjects to all weights, where (n=10). for each group. Scientific coefficients were calculated on (n=16) subjects, (n=8) for each group. Psychological and physiological tests were conducted from 5/3/2012 to 18/3/2012. Main study was conducted from 20/4/2012 to 3/5/2012, where attention aspects, (RT) and (PV) were applied on: - Pulse and blood pressure (BP) before and after effort aerobic and anaerobic ability, vital capacity (VC), and breathing rate before and after performance. Data were collected and statistics was processed and more important conclusions were: 1- Excellence of wrestlers than boxers in attention change and physiological variables (anaerobic ability, vital capacity). 2-Excellence of Boxers than wrestlers in attention aspects (concentration, distribution), (RT), (PV), (aerobic ability), pulse and (BP) after effort. 3-The lack of statistically significant differences of wrestlers and boxers in attention sharpness, physiological variables (pulse and (BP) before effort and breathing rate after performance). 4- There are statistical significant progressive correlation among attention aspects and (PV), (RT) and (PV) for wrestlers and boxers. 5-There are statistical significant progressive correlation among reaction time and (PV), (RT) and (PV) for wrestlers and boxers. 6-There is an inverse correlation statistically significant between the attention aspects and some physiological variables. 7-There is an inverse correlation statistically significant between the reaction time and some physiological variables. Most important recommendations were: 1-Selection of wrestlers according to psychological variables and reaction time depending on their abilities. 2-Selection of boxers according to psychological variables and reaction time depending on their abilities. 3-Taking care of physiological variables to wrestlers and boxers.
Keywords: الانجازات الرياضية -- التربية البدنية -- المعايير الرياضية -- علم النفس الرياضى -- الانتباه الرياضى -- المصارعين والملاكمين